Effects of agricultural practices and crops on soil fauna and soil properties in tropical agroecosystems - Loranger-Merciris, Gladys; Jean-Pierre, Aurélie; Angeon, Valérie; Ozier-Lafontaine, Harry (Pedobiologia, 2025)
At the interface with the other compartments of the earth, soil performs many vital functions for the planet and its inhabitants and is subject to current global changes. Today, more than ever, soil and its management are at the heart of many issues (food security, climate change, environment, health…) and maintaining its biodiversity through appropriate agricultural practices is a key challenge. The overall objective of this study was to assess soil fauna abundance and richness across different tropical cropping systems (intensive versus agroecological) and crop type (tomato, yam, pasture). We assumed that (i) agroecological practices will increase soil fauna abundance and taxonomic richness; (ii) agroecological practices will positively affect the ability of soil fauna to influence soil ecological properties, such as soil aggregation and chemical properties. Our results showed that the abundance and richness of soil macrofauna increased in the agroecological system compared to the conventional system. Our study also showed that crop type influenced soil fauna and should be taken into account to better understand the impact of agricultural practices on soil ecological properties. •How agronomic practices and impact soil fauna and soil ecological properties?•A short-cycle, a semi-perennial and a perennial crop were compared.•For each crop, agroecological and conventional intensive plots were assessed.•Soil fauna increased in the agroecological system regardless of the crop type.•Crop type also influenced soil biodiversity.